Technological Differentiation for Inclusive and Adaptive Islamic Education for Students with Disabilities - Syaidah, Khasnah; Dawam, Ainurrafiq; Yunus, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Inclusive education in Islam affirms every santri’s right to access religious learning; however, this study specifically focuses on inclusive Islamic education for students with disabilities in pesantrens and Islamic schools. In practice, these institutions face persistent challenges, including limited physical accessibility, scarcity of adaptive learning materials, insufficient teacher competencies, and social stigma toward students with special needs. This study aims to theoretically and practically identify approaches, research trends, and gaps related to the integration of differentiated learning and digital technology in inclusive Islamic education. Using a qualitative library research method, this study systematically reviews and thematically analyzes selected peer-reviewed literature published between 2019 and 2024, focusing on differentiated instruction, educational technology in Islamic education, and inclusive practices for students with disabilities. The findings indicate that integrating differentiated content, process, product, and learning environments with digital tools such as e-learning platforms, audio-based tafsir applications, gamified fiqh learning, and assistive media (Braille materials and sign-language videos) enhances learning motivation, conceptual understanding, and classroom participation. Documented case studies show improved student engagement, better access to religious texts, and more adaptive instructional practices. Nevertheless, limited technological infrastructure, low teacher digital literacy, and a lack of locally grounded empirical research remain significant challenges. These findings underscore the importance of technology-based differentiated learning for strengthening inclusive Islamic education and informing adaptive curricula, teacher development, and inclusive educational policies.